Controlled directional ion emission from several fragmentation channels of CO driven by a few-cycle laser field - Betsch, K. J.; Johnson, Nora G.; Bergues, B.; Kübel, M.; Herrwerth, O.; Senftleben, A.; Ben-Itzhak, I.; Paulus, G. G.; Moshammer, R.; Ullrich, J.; Kling, M. F.; Jones, R. R. (My University, 2012)
We explore the dissociative ionization of CO with carrier-envelope-phase (CEP) tagged few-cycle laser pulses. We observe the CEP dependence of the directional emission of Cp+ and Oq+ fragments from transient CO(p+q)+ ions, where p+q≤3 and q≤1. At I0=3.5×1014 W/cm2, a 180∘ phase difference between the C+ and O+ fragments from the (p=1, q=0) and (p=0, q=1) channels reflects the orientation dependence of the CO ionization. At I0=1.2×1015 W/cm2, we find a ∼35∘ phase shift between the C2+ fragments from the (p=2, q=0) and (p=2,q=1) channels, in contrast to the 180∘ shift previously observed between the C2+ fragment channels at I0=6×1014 W/cm2 [Phys. Rev. Lett. 106, 073004 (2011)].